Collusion in Oligopoly: An Experiment on the Effect of Numbers and Information - Dolbear, F. T.; Lave, L. B.; Bowman, G.; Lieberman, A.; Prescott, E.; Rueter, F.; Sherman, R. (Quarterly Journal of Economics, 1968)
I. Introduction, 240. — II. Price variations models of oligopoly, 241. — III. An experimental oligopoly market, 242. — IV. Hypotheses, 248. — V. Procedure, 249. — VI. Results, 251. — VII. Discussion, 257. — VIII. Summary and conclusions, 259.